2019
DOI: 10.1097/mpg.0000000000002181
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Utility of Pediatric Balloon‐assisted Enteroscopy

Abstract: Objectives: The benefit of balloon-assisted enteroscopy (BAE) had been recently documented in pediatric patients, but previous reports are based on single institution experiences. We evaluated the feasibility of pediatric BAE in 8 tertiary referral hospitals throughout Japan. Methods: This was a prospective, multi-institutional study. Patients younger than 18 years were enrolled between April 2014 and March 2017 to undergo double-balloon or single-ballo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Hagiwara et al . reported on the use of 96 procedures of pediatric BAE in multicenter study from Japan in 2019; that study included eight institutions and found that BAE could be safely performed even in children aged ≥ 1 year, with an adverse event rate of 2% 32 . The incidence rate of BAE in this study was 3.1%, echoing previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…Hagiwara et al . reported on the use of 96 procedures of pediatric BAE in multicenter study from Japan in 2019; that study included eight institutions and found that BAE could be safely performed even in children aged ≥ 1 year, with an adverse event rate of 2% 32 . The incidence rate of BAE in this study was 3.1%, echoing previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…By contrast, BAE is often performed under general anesthesia, with reports of intravenous anesthesia being used for older children (age >16 years) 27,28 . Although no detailed description of the choice of anesthesia is provided in each of the papers, 2,14,15,27–40 a clear reference cannot be made, but general anesthesia is often chosen for the trans‐oral route, even in older children, whereas intravenous anesthesia is often chosen for the trans‐anal route. The reasons why general anesthesia is often chosen for the trans‐oral route are as follows: the examination time is long, 15 the airway is easily compressed by the overtube in small children, and it is difficult to ensure intraoperative sedation due to the vomiting reflex.…”
Section: Sedation For Examinationmentioning
confidence: 99%
“…Indications for balloon‐assisted enteroscopy in children. Data obtained from references 2,14,15,23,40,49–53 . IBD, inflammatory bowel disease; OGIB, obscure gastrointestinal bleeding.…”
Section: Indications and Diagnostic Yieldmentioning
confidence: 99%
See 2 more Smart Citations